Tri Hita Karana-Based School Leadership for Shaping Elementary School Graduate Profiles - Krisnayani, Putu Eka; Arnyana, Ida Bagus Putu; Suja, I Wayan (Jurnal Paedagogy, 2026)
This study aims to analyze Tri Hita Karana-based school leadership as a conceptual foundation for shaping elementary school graduate profiles. The study employed a qualitative library research approach by examining educational policy documents, scientific journal articles, books, and other relevant academic publications related to Tri Hita Karana, school leadership, character education, local wisdom-based education, and elementary school graduate profiles. Data were collected through the identification, screening, classification, and synthesis of relevant literature. The data were analyzed using content analysis and thematic analysis, while source triangulation and relevance checking were employed to enhance the credibility of the findings. The results indicate that the three core principles of Tri Hita Karana—Parhyangan, Pawongan, and Palemahan—are closely aligned with the dimensions of elementary school graduate profiles. *Parhyangan* strengthens faith, moral awareness, and ethical behavior; *Pawongan* promotes citizenship, collaboration, communication, empathy, and social responsibility; whereas Palemahan fosters ecological awareness, healthy lifestyles, independence, creativity, and critical thinking. The findings further suggest that leadership grounded in Tri Hita Karana provides a conceptual framework for school principals and teachers to integrate local wisdom into school culture, classroom instruction, co-curricular programs, and students’ daily character development. Overall, this study demonstrates that Tri Hita Karana-based school leadership can serve as a strategic bridge between national graduate competency standards and local wisdom-based education, contributing to the development of elementary school graduates who are academically competent, spiritually grounded, socially responsible, and environmentally conscious.